INTspect: Interrupt Latencies in the Linux Kernel - Herzog, Benedict; Gerhorst, Luis; Heinloth, Bernhard; Reif, Stefan; Honig, Timo; Schroder-Preikschat, Wolfgang (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2018: Anais do VIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2018)
Interrupt handling with predictably low latency is a must for systems to respond to external events. System designers of tiny embedded computers to large-scale distributed systems face the challenge of ever-increasing hardware and software complexity. In the absence of precise timing models, measurement-based approaches are required to achieve predictably low latency. In this paper, we present INTspect, a tool that systematically evaluates the interrupt latency, at run-time, in the Linux operating system kernel. We apply INTspect on two distinct platforms (i.e. ARM and Intel) to measure interrupt latencies, identify jitter causes, and reveal interdependencies between interrupt handlers and user-space workloads. Our tool thus provides valuable insight on interrupt timings and interferences.